2011
DOI: 10.1111/j.1467-6486.2011.01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Employees to Work Beyond Retirement: A Multi‐Level Study of the Role of I‐Deals and Unit Climate

Abstract: The present study investigates what role I-deals (i.e. the idiosyncratic deals made between employees and their organization) play in the motivation of employees to continue working after retirement. We hypothesized two types of I-deals (i.e. development and flexibility I-deals) to be positively related to motivation to continue working. More specifically, we drew from continuity and personality theory to argue that the motivation to continue working is enhanced by I-deals, because they fulfil people's needs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
289
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 202 publications
(302 citation statements)
references
References 74 publications
3
289
1
7
Order By: Relevance
“…The study of Bal et al (2012) showed that flexibility i-deals related to motivation to continue working beyond retirement, while the study of Bal and De Lange (2015) showed that flexibility was related to higher employee engagement and performance. found that use of flexible careers was related to higher employee engagement and subsequent career success, while Pitt-Catsouphes and Matz-Costa (2008) showed that flexibility fit was positively related to employee engagement.…”
Section: Employee Perceptions On Workplace Flexibility For Older Workersmentioning
confidence: 99%
See 4 more Smart Citations
“…The study of Bal et al (2012) showed that flexibility i-deals related to motivation to continue working beyond retirement, while the study of Bal and De Lange (2015) showed that flexibility was related to higher employee engagement and performance. found that use of flexible careers was related to higher employee engagement and subsequent career success, while Pitt-Catsouphes and Matz-Costa (2008) showed that flexibility fit was positively related to employee engagement.…”
Section: Employee Perceptions On Workplace Flexibility For Older Workersmentioning
confidence: 99%
“…The panel study of Golden (2008) among a large sample of US employees revealed a negative relationship between age and having access to flexible work schedules. Moreover, the study of Bal et al (2012) shows a negative correlation between age and flexibility i-deals, indicating that older workers are less likely to negotiate ideals concerning flexibility at work. However, research also shows that older workers in bridge jobs have higher access to flexible work options than older workers in career jobs (ArmstrongStassen, 2008a,b).…”
Section: Employee Perceptions On Workplace Flexibility For Older Workersmentioning
confidence: 99%
See 3 more Smart Citations